Human longevity is associated with regular sleep patterns, maintenance of slow wave sleep, and favorable lipid profile - Mazzotti, Diego Robles; Guindalini, Camila; Moraes, Walter André dos Santos; Andersen, Monica Levy; Cendoroglo, Maysa Seabra; Ramos, Luiz Roberto; Tufik, Sergio (Frontiers in Aging Neuroscience, 2014)
Some individuals are able to successfully reach very old ages, reflecting higher adaptation against age-associated effects. Sleep is one of the processes deeply affected by aging; however few studies evaluating sleep in long-lived individuals (aged over 85) have been reported to date. The aim of this study was to characterize the sleep patterns and biochemical profile of oldest old individuals (N=10, age 85-105 years old) and compare them to young adults (N=15, age 20-30 years old) and older adults (N=13, age 60-70 years old). All subjects underwent full-night polysomnography, one-week of actigraphic recording and peripheral blood collection. Sleep electroencephalogram spectral analysis was also performed. The oldest old individuals showed lower sleep efficiency and REM sleep when compared to the older adults, while stage N3 percentage and delta power were similar across the groups. Oldest old individuals maintained strictly regular sleep-wake schedules and also presented higher HDL-cholesterol and lower triglyceride levels than older adults. The present study revealed novel data regarding specific sleep patterns and maintenance of slow wave sleep in the oldest old group. Taken together with the favorable lipid profile, these results contribute with evidence to the importance of sleep and lipid metabolism regulation in the maintenance of longevity in humans.